Comparison and Advanced Antimicrobial Strategies of Silver and Copper Nanodrug-Loaded Glass Ionomer Cement against Dental Caries Microbes - Amal Adnan Ashour; Mohammed Fareed Felemban; Nayef H. Felemban; Enas T. Enan; Sakeenabi Basha; Mohamed M. Hassan; Sanaa M. F. Gad El-Rab (MDPI AG, 2022)
Caries lesions during cement repairs are a severe issue, and developing a unique antimicrobial restorative biomaterial can help to reduce necrotic lesion recurrence. As a result, Thymus vulgaris extract was used to biosynthesize copper nanoparticles (TVE-CuNPs) exhibiting different characteristics (TVE). Along with TVE-CuNPs, commercial silver nanoparticles (AgNPs) and metronidazole were combined with glass ionomer cement (GIC) to test its antibacterial efficacy and compressive strength. FTIR, XRD, UV-Vis spectrophotometry, and TEM were applied to characterize the TVE-CuNPs. Additionally, AgNPs and TVE-CuNPs were also combined with metronidazole and GIC. The modified GIC samples were divided into six groups, where groups 1 and 2 included conventional GIC and GIC with 1.5% metromidazole, respectively; group 3 had GIC with 0.5% TVE-CuNPs, while group 4 had 0.5% TVE-CuNPs with metronidazole in 1.5%; group 5 had GIC with 0.5% AgNPs, and group 6 had 0.5% AgNPs with metronidazole at 1.5%. An antimicrobial test was performed against Staphylococcus aureus (S. aureus) and Streptococcus mutans (S. mutans) by the disc diffusion method and the modified direct contact test (MDCT). GIC groups 4 and 6 demonstrated a greater antimicrobial efficiency against the two tested strains than the other groups. In GIC groups 4 and 6, the combination of GIC with two antimicrobial agents, 1.5% metronidazole and 0.5% TVE-CuNPs or AgNPs, enhanced the antimicrobial efficiency when compared to that of the other groups with or without a single agent. GIC group specimens combined with nanosilver and nanocopper had similar mean compressive strengths when compared to the other GIC groups. Finally, the better antimicrobial efficacy of GIC boosted by metronidazole and the tested nanoparticles against the tested strains may be relevant for the future creation of more efficient and modified restorations to reduce dental caries lesions.